Theoretic and Experimental Studies on the Casting of Large Die-Type Parts Made of Lamellar Graphite Grey Pig Irons by Using the Technology of Polystyrene Moulds Casting from Two Sprue Cups. (15th October 2012) - Marta, Constantin; Ruja, Ioan; Lupinca, Cinca Ionel; Rosu, Monica
Abstract : This paper presents a comparative analysis between the practical results of pig iron die-type part casting and the results reached by simulation. The insert was made of polystyrene, and the casting was downward vertical. As after the part casting and heat treatment cracks were observed in the part, it became necessary to locate and identify these fissures and to establish some measures for eliminating the casting defects and for locating them. The research method was the comparisons of defects identified through verifications, measurements, and metallographic analyses applied to the cast part with the results of some criteria specific to simulation after simulating the casting process. In order to verify the compatibility between reality and simulation, we then simulated the part casting respecting the real conditions in which it was cast. By visualising certain sections of the cast part during solidification, relevant details occur about the possible evolution of defects. The simulation software was AnyCasting, the measurements were done through nondestructive methods.